The tale teller [compact disc, unabridged] - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel., 2019)
Legendary Navajo policeman Lieutenant Joe Leaphorn takes center stage in this riveting atmospheric mystery from New York Times bestselling author Anne Hillerman that combines crime, superstition, and tradition and brings the desert Southwest vividly alive. Joe Leaphorn may have retired from the Tribal Police, but he finds himself knee-deep in a perplexing case involving a priceless artifact--a reminder of a dark time in Navajo history. Joe's been hired to find a missing biil, a traditional weaving that had been donated to the Navajo Nation. His investigation takes a sinister turn when the leading suspect dies under mysterious circumstances and Leaphorn himself receives anonymous warnings to beware--witchcraft is afoot.